Bibliometric Analysis of Islamic Education Research Development in Scopus International Database Publications 2018-2022: Analisis Bibliometrik Perkembangan Penelitian Pendidikan Islam dalam Publikasi Internasional pada Database Scopus 2018-2022 - Jannah, Miftahul; Hakiman; Ramadhan, Syahrul (SHAHIH: Journal of Islamicate Multidisciplinary, 2022)
This research aims as literature or library material that can be used in mapping the writing of further Islamic Education scientific articles. By knowing the main information of the article, the most relevant authors, developments of publication by year, productive countries, co-occurrence network by title, source titles, theme developments, trending topics by title, wordcloud by title, thematic maps, most citations, and institutional network collaborations.the tool used to analyze the data in this study is part of the r-studio, namely the software bibliometrix r-package. the analyzed data were obtained from the scopus database with journal document types. the type of document obtained is in the form of a bibtex file extension that is analyzed using the biblioshiny webinterface. the results of a bibliometric analysis of the scientific study of Islamic Education provide an illustration that scientific articles on Islamic Education are quite popular in the world of global academia. Furthermore, the collaboration of institutional networks in scientific studies of Islamic Education is still dominated by universities in Muslim-majority countries. The discussion of the scientific study of Islamic Education raised many themes related to the social field, the concept of Islamic Education in general, and Islamic Education which was integrated with several other concepts such as entrepreneurship, Islamic Education in Indonesia, and others. The development of studies on Islamic Education follows global developments where from 2020 until now researchers have discussed a lot about Islamic Education which is connected to the Covid-19 Pandemic situation.